APPLICATIONS OF GIGER AND DAVIDHIZAR'S TRANSCULTURAL NURSING THEORY IN INDONESIA - Astuti, Reini; Alzate, Agaton Manuel T. (STIKes Budi Luhur Cimahi, 2022)
Indonesia has a diversity of cultures and ethnic groups. Indonesia is an archipelagic country that includes more than 17,000 islands inhabited by around 255 million people, making Indonesia the fourth most populous country in the world. This figure also implies that many cultural, ethnic, religious and linguistic diversity can be found in this country. The culture varies greatly, from Hindu rituals practised daily on the island of Bali to the (partial) implementation of sharia law in Aceh and the hunter-gatherer lifestyle of the Mentawai people. The relationship between culture and health is very close. Cultural diversity and customs have various influences on health behaviour. Each ethnic group has different customs and norms from one another. In an area, they can process natural resources in their area as a cure for a disease with their skills and knowledge, which cannot escape the preserved hereditary traditions. This causes health workers to have exceptional attention to patient culture when they provide health services in the community. Moreover, for a nurse, Indonesian nurses should have the ability and knowledge of various cultures in Indonesia to provide culturally sensitive nursing care to patients. Nursing care given to patients by paying attention to the cultural aspects and customs of the client tends to have an optimal healing effect. Keywords : Nursing theory, Giger and Davidhizar, Transcultural, Indonesia